2018
DOI: 10.1186/s13006-018-0175-8
|View full text |Cite
|
Sign up to set email alerts
|

Fish intake reflects on DHA level in breast milk among lactating women in Latvia

Abstract: BackgroundDocosahexaenoic acid (DHA) is an essential fatty acid required for proper growth and development. DHA levels in breast milk vary worldwide. Higher levels are observed among coastal populations and are associated with marine food consumption. Latvia is located in Northern Europe, on the eastern shore of the Baltic Sea. Nevertheless, fish consumption among women of reproductive age is low. The aim of this study was to determine DHA levels in breast milk among lactating women in Latvia.MethodsInvitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 34 publications
1
24
1
8
Order By: Relevance
“…It is worth noting that both n -3 LC PUFA and carotenoid concentration in breastmilk are diet-dependent [41,68,69,70]. The DHA concentration in breastmilk may be increased through the consumption of fish [70] or dietary supplementation, both during lactation and pregnancy [71,72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that both n -3 LC PUFA and carotenoid concentration in breastmilk are diet-dependent [41,68,69,70]. The DHA concentration in breastmilk may be increased through the consumption of fish [70] or dietary supplementation, both during lactation and pregnancy [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that both n -3 LC PUFA and carotenoid concentration in breastmilk are diet-dependent [41,68,69,70]. The DHA concentration in breastmilk may be increased through the consumption of fish [70] or dietary supplementation, both during lactation and pregnancy [71,72]. The previous studies showed that a DHA dose of 1.0–7.5 g/day was safe for mothers and infants and was linked with other health benefits in adults, including cardiovascular and brain function in adults [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is not consistent with previous studies conducted in the United States [31,32], Canada [17,33], and Europe [34], which reported that the majority of breastfeeding women in the Alberta Pregnancy Outcomes and Nutrition (APrON) cohort were not meeting any of the various authorities’ omega-3 FAs recommendations [35]. Similarly, in the Latvian study (Latvia and Poland are situated in the same geographic region, both countries have access to the Baltic Sea), DHA daily intake was lower than recommended, and was only 136 ± 26 mg [36]. It is widely reported that supplementation increases mother’s milk DHA concentrations [37,38], and our results confirmed these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Fat content in human milk was determined by LVS ISO 2446:2008, protein content was determined by LVS EN ISO 8968-1:2014 (conversion factor of 6.25 was used), lactose was determined by ISO 22662:2007, and the fatty acid profile of human milk was analyzed using gas chromatography (for a more detailed description, see Aumeistere et al, 2018 [21]).…”
Section: Methodsmentioning
confidence: 99%